Perceived Impact of Site Personnel and Infrastructure on Monitoring Quality in Clinical Trials: a Survey of Italian CRA/CTM Professionals - Stefano Stabile; Sara Testoni; Emanuela Scarpi; Veronica Franchina; Francesca Mannozzi; Marta Betti; Alessandra Ferrari; Celeste Cagnazzo (Journal of Pharmaceutical Innovation, 2026)

Flies from meat processing facilities are carriers of multidrug-resistant Escherichia coli and diverse Staphylococcaceae species - Matheus Zorzal Bernardes Rangel; Gustavo Guimarães Fernandes Viana; Ana Julia Camuzzi Ferrari Storck; Carolina Magri Ferraz; Sarah Bernardes Simões; Valéria Modolo Peterle; Natalia Pereira; Pamella Almeida Freire Casemiro; Alessandra Figueiredo de Castro Nassar; Vanessa Castro; Bruna Maria Salotti-Souza; Juliano Gonçalves Pereira; et al. (Brazilian Journal of Microbiology, 2026)
Flies are important vectors of antimicrobial resistance (AMR) in food production, but their role in meat processing environments remains poorly characterized. This study isolated Enterobacteriaceae and Staphylococcaceae (including Mammaliicoccus sciuri ) from flies collected in bovine and swine slaughterhouses and meat processing industries. Phenotypic AMR was assessed, and the presence of selected antimicrobial resistance and virulence genes ( mecA , sea , see , sec , stx1 , stx2 , and eae ) was verified. Out of 60 flies collected, a total of 34 isolates were identified using MALDI-TOF with 13 different bacterial species, including Escherichia coli , Citrobacter braakii , C. freundii , Klebsiella pneumoniae , Hafnia alvei , Enterobacter kobei , S. aureus , S. epidermidis , S. saprophyticus , S. simulans , S. warneri , S. xylosus , and M. sciuri . Among Staphylococcaceae isolates, 17.6% were resistant to oxacillin and 23.5% to gentamicin. Regarding the Enterobacteriaceae isolates, 41.2% were resistant to streptomycin. Ten isolates (two E. coli , one S . epidermidis , two S. saprophyticus , one S. simulans , one S . warneri and three M. sciuri ) were considered multidrug-resistant (MDR). Notably, none of the targeted genes ( mecA , sea , see , sec , stx1 , stx2 , eae ) were detected by PCR. These findings suggest that flies can disseminate important resistant opportunistic bacteria in meat processing environments, posing concerns due to the capacity of flies to transmit these bacteria across food, processing facilities, animals and humans. These results underscore the need for continuous AMR surveillance and effective vector control to reduce the risks posed by flies in meat processing environments.

Exploring the prognostic implications of programmed death-ligand 1 expression in canine nodal lymphoma: Insights from surface membrane expression, transcript amount and plasmatic levels - Alessandra Ubiali; Luiza Cesar Conti; Raffaella De Maria; Paola Emanuela Maria Dall'Ara; Laura Marconato; Roberta Ferrari; Damiano Stefanello; Maria Amati; Luca Aresu; Fulvio Riondato; Valeria Martini (Research in Veterinary Science, 2026)

eIF6 links histone acetylation with translational control of HDAC in skeletal muscle - Alessandra Scagliola; Annarita Miluzio; Ivan Ferrari; Daniel Brina; Sara Ricciardi; Stefano Biffo (Molecular and Cellular Biochemistry, 2026)
Skeletal muscle is crucial for glucose regulation and amino acid storage, significantly influencing overall metabolic balance. Its function is tightly regulated by complex mechanisms, with histone acetylation as a key epigenetic control point. Our previous work identified eIF6 as a key regulator of muscle energy homeostasis and demonstrated its role in modulating histone acetylation in the liver. However, whether similar epigenetic mechanisms underpin eIF6’s effects in muscle remains undetermined. To investigate this, we measured H3K9 acetylation levels and HDAC activity both in vivo, using eIF6 +/– mice, and in vitro, following eIF6 depletion. Our findings demonstrate that eIF6 downregulation in C2C12 myoblasts drives an increase in histone acetylation, a pattern also evident in heterozygous eIF6 primary satellite cells, both in their undifferentiated state and following differentiation. In vivo, eIF6 +/− mice show pronounced histone hyperacetylation, especially in younger animals, which correlates with a specific decrease in class II HDACs, particularly HDAC4 and HDAC5. This trend is further supported by in vitro data and findings from Drosophila eIF6 +/− mutants, both of which exhibit decreased HDAC activity. Importantly, the reduction in HDAC4 and HDAC5 activity appears to result from decreased protein levels, driven by eIF6-dependent translational regulation of their mRNAs. All together, these findings establish a link between mRNA translation and histone acetylation in muscle, underpinning translational control as a master regulator of histone acetylation.

Microbiological quality and allergen assessment of vegan-labelled foods sold in Turin - Sara Morello; Carla Ferraris; Clara Tramuta; Alessandra Provera; Samantha Lupi; Aitor Garcia-Vozmediano; Cristiana Maurella; Daniela Manila Bianchi (Journal of Consumer Protection and Food Safety, 2026)
The consumption of vegan-labelled foods has increased due to ethical, environmental, and health motivations, yet comprehensive evaluations of their microbiological safety and undeclared animal-derived allergens remain limited. This study analyzed 34 vegan products from Turin, Italy, using microbiological assays alongside biomolecular and immunoenzymatic techniques to detect crustacean and vertebrate DNA, as well as milk and egg proteins. Results showed no presence of Salmonella spp ., Listeria monocytogenes , milk, egg, or crustacean allergens; Enterobacteriaceae were detected within acceptable limits in 2 samples, and vertebrate DNA was found in one non-dairy cheese alternative. Overall, these findings indicate generally good hygienic quality and effective allergen management in the analysed products. These results provide baseline evidence to support future risk assessments and regulatory considerations in the plant-based food sector.

Nodal lymphatic mapping in 22 dogs bearing solid malignant tumors and enlarged regional lymph nodes: A descriptive study (2022–2025) - Elisa Maria Gariboldi; Alessandra Ubiali; Roberta Ferrari; Luigi Auletta; Donatella De Zani; Davide Danilo Zani; Francesco Ferrari; Federica Alessandra Brioschi; Paola Roccabianca; Chiara Giudice; Valeria Grieco; Camilla Recordati; et al. (The Veterinary Journal, 2026)

From molecules to organisms: A multi-level approach shows negative effects of trace elements from sewage sludge used as soil improver on honeybees - Andrea Ferrari; Michela Sturini; Beatrice De Felice; Francesco Bonasoro; Chiara Francesca Trisoglio; Marco Parolini; Roberto Ambrosini; Luca Canova; Antonella Profumo; Federica Maraschi; Carlo Polidori; Alessandra Costanzo (Journal of Hazardous Materials, 2024)

Clinical effects of perineural dexmedetomidine or magnesium sulphate as adjuvants to ropivacaine in dogs undergoing tibial plateau leveling osteotomy - Federica Alessandra Brioschi; Vanessa Rabbogliatti; Luigi Auletta; Giuliano Ravasio; Martina Amari; Luigi Elia; Ilaria Gritti; Francesco Ferrari (Research in Veterinary Science, 2024)

Effect of cranial tibial artery laceration on radiographic bone healing and perioperative complications in dogs undergoing tibial plateau leveling osteotomy - Francesco Ferrari; Roberto Tamburro; Maurizio Longo; Federica Alessandra Brioschi; Luigi Auletta; Damiano Stefanello (Research in Veterinary Science, 2024)

Initial Trajectory Assessment of a low-thrust option for the RAMSES Mission to (99942) Apophis - Andrea C. Morelli; Alessandra Mannocchi; Carmine Giordano; Fabio Ferrari; Francesco Topputo (Advances in Space Research, 2024)

Statistical significance of curing variables on geopolymerization of mining by-product untreated clay - Caterina Sgarlata; Francesco Edoardo Vaccari; Alessandra Formia; Francesco Ferrari; Cristina Leonelli (Applied Clay Science, 2024)

The Frequency of Intermediate Alleles in Patients with Cerebellar Phenotypes - Elena Capacci; Silvia Bagnoli; Giulia Giacomucci; Costanza Maria Rapillo; Alessandra Govoni; Valentina Bessi; Cristina Polito; Irene Giotti; Alice Brogi; Elisabetta Pelo; Sandro Sorbi; Benedetta Nacmias; et al. (The Cerebellum, 2023)
Cerebellar syndromes are clinically and etiologically heterogeneous and can be classified as hereditary, neurodegenerative non-hereditary, or acquired. Few data are available on the frequency of each form in the clinical setting. Growing interest is emerging regarding the genetic forms caused by triplet repeat expansions. Alleles with repeat expansion lower than the pathological threshold, termed intermediate alleles (IAs), have been found to be associated with disease manifestation. In order to assess the relevance of IAs as a cause of cerebellar syndromes, we enrolled 66 unrelated Italian ataxic patients and described the distribution of the different etiology of their syndromes and the frequency of IAs. Each patient underwent complete clinical, hematological, and neurophysiological assessments, neuroimaging evaluations, and genetic tests for autosomal dominant cerebellar ataxia (SCA) and fragile X-associated tremor/ataxia syndrome (FXTAS). We identified the following diagnostic categories: 28% sporadic adult-onset ataxia, 18% cerebellar variant of multiple system atrophy, 9% acquired forms, 9% genetic forms with full-range expansion, and 12% cases with intermediate-range expansion. The IAs were six in the FMR1 gene, two in the gene responsible for SCA8, and one in the ATXN2 gene. The clinical phenotype of patients carrying the IAs resembles, in most of the cases, the one associated with full-range expansion. Our study provides an exhaustive description of the causes of cerebellar ataxia, estimating for the first time the frequency of IAs in SCAs- and FXTAS-associated genes. The high percentage of cases with IAs supports further screening among patients with cerebellar syndromes.

Detection and genetic characterization of domestic cat hepadnavirus in cats with cavitary effusions - Gabriele Ratti; Angelica Stranieri; Donatella Scavone; Alessandra Cafiso; Sara Meazzi; Camilla Luzzago; Paola Dall’Ara; Filippo Tagliasacchi; Laura Cavicchioli; Francesco Ferrari; Alessia Giordano; Saverio Paltrinieri; et al. (Veterinary Microbiology, 2023)

Thermal expansion of oldhamite, CaS: Implication for the surface of Mercury - Anna Barbaro; Federico Zorzi; Alessandra Lorenzetti; Sabrina Ferrari; Cristina Tubaro; Fabrizio Nestola (Icarus, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Simultaneous extraction of calcium phosphates and proteins from fish bones. Innovative valorisation of food by-products - Alessio Adamiano; Stefania Scialla; Francesca Carella; Marialuisa Casella; Serena Camerini; Alessandra Quarta; Alexandra Muntiu; Francesca Ferrari; Alberto Vitali; Michele Iafisco; Clara Piccirillo (Journal of Cleaner Production, 2023)

In vitro antiglycation and antioxidant properties of Eugenia pyriformis leaves and fruits - Giselle Lopes da Silva; Mariana Bordin Campideli; Anna Beatriz Sabino Ferrari; Helena Mannochio-Russo; Karina Fraige; Alessandra Cristina Dametto; Vanderlan da Silva Bolzani; Maria Luiza Zeraik (Natural Product Research, 2022)

Virtual-Reality Performance-Based Assessment of Cognitive Functions in Adult Patients With Acquired Brain Injury: A Scoping Review - Claudia Corti; Maria Chiara Oprandi; Mathilde Chevignard; Ashok Jansari; Viola Oldrati; Elisabetta Ferrari; Monica Martignoni; Romina Romaniello; Sandra Strazzer; Alessandra Bardoni (Neuropsychology Review, 2022)

How social is the cerebellum? Exploring the effects of cerebellar transcranial direct current stimulation on the prediction of social and physical events - Viola Oldrati; Elisabetta Ferrari; Niccolò Butti; Zaira Cattaneo; Renato Borgatti; Cosimo Urgesi; Alessandra Finisguerra (Brain Structure and Function, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Cumulative intracranial tumour volume prognostic assessment: a new predicting score index for patients with brain metastases treated by stereotactic radiosurgery - Carmine Antonio Donofrio; Andrea Cavalli; Marco Gemma; Lucia Riccio; Alessandra Donofrio; Pietro Panni; Camillo Ferrari da Passano; Antonella Del Vecchio; Angelo Bolognesi; Riccardo Soffietti; Pietro Mortini (Clinical & Experimental Metastasis, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Dynamics of Mycoplasma hyopneumoniae seroconversion and infection in pigs in the three main production systems - Enrico Giacomini; Nicola Ferrari; Alessandra Pitozzi; Michela Remistani; Daniele Giardiello; Dominiek Maes; Giovanni Loris Alborali (Veterinary Research Communications, 2016)

Combination of Pretreatment with White Rot Fungi and Modification of Primary and Secondary Cell Walls Improves Saccharification - Charis Cook; Fedra Francocci; Felice Cervone; Daniela Bellincampi; Paul G Bolwell; Simone Ferrari; Alessandra Devoto (BioEnergy Research, 2015)

Adverse reactions related to drugs for headache treatment: clinical impact - Anna Ferrari; Alessandra Ottani; Alfio Bertolini; Arrigo Francesco Giuseppe Cicero; Ciro Pio Rosario Coccia; Sheila Leone; Emilio Sternieri (European Journal of Clinical Pharmacology, 2005)

Mutational scanning of the ABCR gene with double-gradient denaturing-gradient gel electrophoresis (DG-DGGE) in Italian Stargardt disease patients - Antonella Fumagalli; Maurizio Ferrari; Nadia Soriani; Alessandra Gessi; Barbara Foglieni; Elisabetta Martina; Maria Manitto; Rosario Brancato; Michael Dean; Rando Allikmets; Laura Cremonesi (Human Genetics, 2001)